NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PUNGGAHAN RAMADHAN - Surawardi Surawardi; Ardiyan Fikrianoor (Program Studi PAI STAI Al Falah Banjarbaru, 2023)
Abstract: The punggahan tradition is a tradition that aims to manifest gratitude and ask Allah SWT. the month of Ramadan is coming. The punggahan tradition is carried out one day before entering the month of Ramadan in one of the community houses or prayer rooms to gather with the contents of congregational evening prayers, reading tahlil, yasin, joint prayers sent to ancestors and eating together. The increasingly modern era is a challenge for society to be able to preserve the traditions that are already attached. As a result of the development of the era, knowledge of tradition is decreasing because it is considered only as a habit without knowing the meaning in it. The purpose of this study was to find out the implementation of the Ramadan fasting tradition in Batu Meranti Village, to find out the Islamic educational values contained in the Ramadan fasting tradition and the value of religious moderation contained in the poetry tradition. The researcher used a qualitative descriptive analysis method to collect the results of interviews or observations regarding the problems that occurred in the field. The researcher found that the results of the punggahan tradition research carried out in Batu Meranti village contained four Islamic educational values, namely: the value of community belief, the value of worship which is manifested in praying and giving charity, the value of morality and muamalah is manifested by mutual respect for one another. Even though the era is now modern, the tradition of punggahan in Batu Meranti Village is still sustainable because parents care about the tradition. This is very important to be absorbed by the younger generation that the social sustainability of the environment in the future is in the hands of the younger generation. Religious moderation is reflected in the implementation of traditions that are not extreme, follow Islamic teachings and respect one another. Keywords: Education, Islam, Punggahan Traditions, Values. Abstrak: Tradisi punggahan adalah tradisi yang bertujuan untuk mewujudkan rasa syukur dan memohon kepada Allah SWT. akan datangnya bulan ramadhan. Tradisi punggahan dilaksanakan satu hari sebelum masuk bulan ramadhan di salah satu rumah masyarakat atau mushola untuk berkumpul dengan isi kegiatan sholat magrib berjamaah, membaca tahlil, yasin, doa bersama yang dikirimkan kepada leluhur dan makan bersama. Zaman yang semakin modern menjadi tantangan bagi masyarakat untuk tetap dapat melestarikan tradisi yang sudah melekat. Akibat berkembangnya zaman pengetahuan akan tradisi menjadi semakin menurun karena menganggap hanya sebatas kebiasaan tanpa mengetahui makna yang ada di dalamnya. Tujuan penelitian ini untuk mengetahui pelaksanaan tradisi punggahan ramadhan di Desa Batu Meranti, mengetahui nilai-nilai pendidikan Islam yang terkandung dalam tradisi punggahan ramadhan dan nilai moderasi beragama yang terdapat dalam tradisi punggahan. Peneliti menggunakan metode analisis deskriptif kualitatif dikumpulkan berupa hasil wawancara atau pengamatan mengenai masalah yang diteliti yang terjadi di lapangan. Peneliti mendapatkan hasil penelitian tradisi punggahan yang dilaksanakan di desa Batu Meranti ini mengandung empat nilai-nilai pendidikan Islam, yaitu: Nilai keyakinan masyarakat, nilai ibadah yang diwujudkan dalam berdoa serta bersedekah, nilai akhlak dan muamalah diwujudkan dengan saling menghargai satu sama lain. Walaupun zaman sudah modern tradisi punggahan di Desa Batu Meranti ini tetap lestari karena pedulinya orang tua terhadap tradisi. Hal ini sangat penting diresapi oleh generasi muda bahwa keberlangsungan sosial lingkungan di masa depan ada pada tangan generasi muda. Moderasi beragama tercermin dalam pelaksanaan tradisi yang tidak ekstrim, mengikuti ajaran Islam dan saling menghargai satu sama lain. Kata Kunci: Islam, Nilai-Nilai, Pendidikan, Tradisi Punggahan.